EFEK PROTEKTIF EKSTRAK ETANOL HERBA PEGAGAN (Centella asiatica (L.) Urban) TERHADAP PEMBENTUKAN KATARAK TIKUS WISTAR YANG DIINDUKSI SODIUM SELENIT - Yuliani, Sapto (Universitas Ahmad Dahlan, 2012)
Cataract is one of the eye pathology that can cause blindness. Oxidative stresshas been identified as an initiating factor of cataract. The objective research was tostudy the protective effect of ethanol extract Centela asiatica toward cataract formationon Wistar rat induced by sodium selenite. Cataract was induced in 9 days old Wistarrat, which 5 groups of 7 each. Group I got injection aquadest and the test groups gotinjection CMC-na (group II), vitamin E dose 378 IU/kg bw (group III), ethanol extractGotu cola herb dose 100 mg/kg bw (group IV), and 200 mg/kg bw (group V), 400mg/kgbw, subcutaneously, respectively, for 3 days. After 4 hours, all rats got injection asingle dose 50 ug/kg of BW sodium selenite intraperitoneally. Then eyes were observedin all groups on postnatal day 16, when the eyes of the rat first opened. Then percentageof cataract incidence were calculated. Finally, rats were executed and eyes were takenfor lens histophatological analyses with hematoxiline eosin staining. Based onmacroscopic and microscopic analyses it can be concluded that ethano extract ofCentella asiatica had protective effect toward cataract formation on Wistar rat inducedby sodium selenite. The least cataract incidence was showed at dose 200 mg/kg bw.